Inter‐country exploration of factors associated with admission to long‐term institutional dementia care: evidence from the RightTimePlaceCare study. (14th April 2015) - Verbeek, Hilde; Meyer, Gabriele; Challis, David; Zabalegui, Adelaida; Soto, Maria E.; Saks, Kai; Leino‐Kilpi, Helena; Karlsson, Staffan; Hamers, Jan P.H.; the RightTimePlaceCare Consortium
Abstract Aim To explore inter‐country variation of factors associated with institutionalization of people with dementia. Background There is an urgent need for evidence on whether factors associated with admission to institutional dementia care are applicable across healthcare systems, as increasing evidence suggests that these factors could be country‐specific. Design A prospective cohort study. Method Primary data were collected in eight European countries, at baseline and after 3 months follow‐up (November 2010–April 2012). The sample included 2014 dyads of people with dementia and their informal caregivers; 791 patients were recently institutionalized, 1223 patients lived at home and were at risk of institutionalization. Associations between care setting (institution vs. home) and factors shown to influence institutionalization (e.g. cognition, independence in activities of daily life, behaviour) were studied. Results Considerable differences were found between the eight countries in characteristics of people with dementia who had been recently admitted to ILTC. However, caregiver burden appeared the most consistent factor associated with institutionalization in all analyses. Indications for the importance of independence in activities of daily life were found as well, although country differences may be more prominent for this factor. Conclusion Evidence was found for two common factors, crucial in the process of institutionalization across countries: caregiver burden and independency in activities of daily life. However, this study also suggests that admission to institutional dementia care is context‐specific, as wide variation exists in factors associated with institutionalization across countries. Tailored best‐practice strategies are needed to reflect variations in response to these needs.